Respuesta :

Answer:

  • 6(x^2 +18z +81) . . . as written
  • 6(x +9)^2 . . . . . . . . assuming a typo

Step-by-step explanation:

As the expression is written, the only factoring that can be done is to factor out the common numeric factor of 6:

  = 6(x^2 +18z +81)

__

Assuming a typo in the question

If we assume all variables are supposed to be "x", then the quadratic term can be further factored as a square:

  = 6(x +9)^2

_____

It is often handy to remember that the form of the square of a binomial is ...

  (a +b)^2 = a^2 +2ab +b^2

Here, we recognize that 18 = 2√81, so the binomial is (x +√81) = (x +9).

ACCESS MORE